2008
DOI: 10.1016/j.biocel.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Proteases and cystic fibrosis

Abstract: Cystic fibrosis is the most common, inherited fatal disease in Caucasians. The major cause of morbidity and mortality is chronic lung disease due to infection and inflammation in the airways leading to bronchiectasis and respiratory failure. The signature pathologic features of CF lung disease including abnormal mucus obstructing airways, chronic infection with S. aureus, P. aeruginosa and other gram negative bacteria, and a robust neutrophil-dominant airway inflammation, are exacerbated by unopposed proteases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 102 publications
6
159
1
1
Order By: Relevance
“…For example, recent studies showed that neutrophil elastase (NE), a major product released from activated neutrophils that has recently been identified as a key risk factor for the development of bronchiectasis in young children with CF diagnosed by newborn screening [38], is also a potent regulator of CFTR and ENaC. Besides its previously described roles in the modulation of airway inflammation, mucus hypersecretion, bacterial killing, and proteolytic lung and immune cell damage [32,[39][40][41][42], NE can activate ENaC by proteolytic cleavage and removal of ''inhibitory'' segments, probably leading to a conformational change of the channel that improves its conductivity for Na + [43,44]. Interestingly, a recent study showed that wild-type CFTR, but not DF508, interacts with ENaC in the plasma membrane of airway epithelial cells and, thus, may impede the proteolytic stimulation of ENaC by NE and potentially other extracellular proteases released by inflammatory cells [45,46].…”
Section: Airway Proteases Aggravate Basic Cf Ion Transport Defectmentioning
confidence: 99%
“…For example, recent studies showed that neutrophil elastase (NE), a major product released from activated neutrophils that has recently been identified as a key risk factor for the development of bronchiectasis in young children with CF diagnosed by newborn screening [38], is also a potent regulator of CFTR and ENaC. Besides its previously described roles in the modulation of airway inflammation, mucus hypersecretion, bacterial killing, and proteolytic lung and immune cell damage [32,[39][40][41][42], NE can activate ENaC by proteolytic cleavage and removal of ''inhibitory'' segments, probably leading to a conformational change of the channel that improves its conductivity for Na + [43,44]. Interestingly, a recent study showed that wild-type CFTR, but not DF508, interacts with ENaC in the plasma membrane of airway epithelial cells and, thus, may impede the proteolytic stimulation of ENaC by NE and potentially other extracellular proteases released by inflammatory cells [45,46].…”
Section: Airway Proteases Aggravate Basic Cf Ion Transport Defectmentioning
confidence: 99%
“…Secreted actively (as a consequence of cell activation) or passively (as a consequence of necrotic cell death), neutrophil serine proteases (NSPs; e.g., neutrophil elastase [NE], cathepsin G [CG], and proteinase 3 [PR3]) are major contributors to neutrophil dysfunction. NE is considered a major contributor to a range of pulmonary pathologies, including cystic fibrosis (CF) (1)(2)(3), and is an important therapeutic target (3). Under well-controlled conditions in otherwise healthy individuals, NSPs contribute to the effective control of infection.…”
mentioning
confidence: 99%
“…This cleavage step releases soluble CXCR1, which stimulates IL-8 production by airway epithelial cells, thereby initiating a feedback circuit that amplifies neutrophil recruitment within the CF airways [46]. Extracellular neutrophil elastase can also [47]:…”
Section: Why Is It Important To Identify Molecular Factor(s) Associatmentioning
confidence: 99%